Enunciação e encenação na construção da narrativa fílmica em a mulher do lado, de François Truffaut - Cardoso, Tânia Cardoso de (Universidade do Vale do Rio dos Sinos, 2011)
This paper presents a critical analysis of The woman next door (La femme d’à côté, 1982), penultimate film directed by François Truffaut, based on two analytical axes. At the first axis, trying to understand how is the construction of a filmic narrative from the reflections with respect to the cinematographic enunciation, as elaborated by Arlindo Machado – in his book O sujeito na tela: modos de enunciação no cinema e no ciberespaço - and by André Gaudreault and François Jost – in their book Le récit cinématographique. In the second axis, seeking to understand the narrative from a denotative stylistic approach bringing questions related to the framing and the staging, which are in the heart of the mise-en-scène. We bring as a reference the analysis of David Bordwell, mainly from his book Figures traced in light: on cinematic stading. This author rightly calls into question the idea of enunciation and the importance of the existence of a filmic narrator in a filmic narrative theory. Our objective is to demonstrate how in fact these two analytical axis, that are presented as contradictory, may be complementary to accomplish a broader filmic analysis. François Truffaut’s film serves as a case example for the proposed analysis.
Keywords: Narrativa fílmica; Enunciação cinematográfica; Encenação; Enquadramento; Filmic narrative; Cinematographic enunciation; Staging; Framing